Предмет: Алгебра, автор: emiliagritsyuik

срочно,пожалуйста помогите(a^-2+b^-2):(a^+b^2)

Ответы

Автор ответа: filuksistersp735lh
1

Ответ:

 \frac{ {a}^{ - 2} +  {b}^{ - 2}  }{ {a}^{2} +  {b}^{2}  }  =  \frac{ \frac{1}{ {a}^{2} } +  \frac{1}{ {b}^{2} }  }{ {a}^{2} +  {b}^{2}  }  =   \frac{  \frac{{b}^{2} +  {a}^{2}} { {a}^{2} {b}^{2}  }  }{ {a}^{2} +  {b}^{2}  } =   \\  =  \frac{ {b}^{2}  +  {a}^{2} }{ {a}^{2}  {b}^{2} }  \times  \frac{1}{ {a}^{2} +  {b}^{2}  }  =  \frac{1}{ {a}^{2}  {b}^{2} }  =  {a}^{ - 2}  {b}^{ - 2}  = ( {ab})^{  - 2}

Похожие вопросы
Предмет: Русский язык, автор: zajlaubajramazan47